Environmental constraints of the invasive Mnemiopsis leidyi in Scandinavian waters. (25th November 2012) - Haraldsson, Matilda; Jaspers, Cornelia; Tiselius, Peter; Aksnes, Dag L.; Andersen, Tom; Titelman, Josefin
Abstract : We studied the seasonal dynamics of the invasive ctenophore Mnemiopsis leidyi over its distribution range from Skagerrak into the Baltic Proper during 1 yr and related this to ambient physical and biological variables. The appearance of M. leidyi was sporadic in the Baltic Proper, with 60‐fold lower abundance than in the Skagerrak and Kattegat (mean 0.02 individual m −3 and 1.16 individual m −3, respectively). M. leidyi typically resided above the halocline (10‐20 m depth), except in the Baltic Proper where they were found deeper. Smaller size classes were underrepresented in the Baltic Proper, indicating failed reproduction or high mortality of the younger life stages. Ninety percent of the M. leidyi were observed at salinities of 22‐29 and 75% of the individuals in water masses warmer than 11°C, i.e., typical late summer to autumn temperatures. Results of a Generalized Additive Model (GAM) indicate that the spatio‐temporal distribution of M. leidyi might be explained by advection of M. leidyi from the Skagerrak and Kattegat area to the Baltic Proper. We conclude that the low salinity (< 9) of the Baltic Proper is likely to restrict successful reproduction and establishment of M. leidyi and that the advection of individuals from higher saline source areas sustained the observed Baltic Proper occurrence.